Role of Polyphosphate Kinase in Biofilm Formation by Porphyromonas gingivalis - Chen, Wen (American Society for Microbiology, 2002)
In order to assess the role of polyphosphate kinase (PPK) in the physiology of Porphyromonas gingivalis, a ppk gene mutant, CW120, was constructed and characterized. P. gingivalis was demonstrated to synthesize short-chain polyphosphate (polyP) but not long-chain polyP. CW120 failed to survive in the stationary phase as well as the parental cell did, and it was attenuated in biofilm formation on polyvinylchloride and glass surfaces. Furthermore, the complementation by insertion of an intact copy of the ppk gene into the mutant CW120 restored its biofilm formation and stationary-phase survival. These results suggest that PPK may be important for incorporation of these organisms into subgingival plaque in the human oral cavity.